Multi-criteria decision-making for the life cycle of sustainable high pressure die casting products. (23rd April 2020) - Pagone, Emanuele; Papanikolaou, Michail; Salonitis, Konstantinos; Jolly, Mark
In the scientific literature there is a scarcity of comprehensive and organic studies on performance indicators encompassing sustainability and their influence on decision-making. This work aims at selecting the most suitable material to manufacture an automotive component using a high pressure die casting (HPDC) process according to four classes of metrics: cost, time, quality and sustainability. The performance of three different alloys (aluminium-A380, magnesium-AZ91D and zinc-ZA8) was evaluated considering overall product life cycle aspects and process characteristics through a deterministic technique for order of preference by similarity to ideal solution (TOPSIS). Results show that the zinc alloy should be chosen on a unit mass-basis mainly thanks to its significantly superior quality and sustainability performance. This study demonstrates that the inclusion of the sustainability dimension in a multi-criteria decision analysis context challenges well-established material selection trends in the automotive industry developed during the past decades.